ANALISIS PENDAPATAN USAHATANI KAKAO DI DESA BOBO KECAMATAN PALOLO KABUPATEN SIGI - Jaib, Abd.; Muis, Abdul; Howara, Dafina (AGROTEKBIS, 2019)
Agricultural development aims to increase the yield and quality of production, increasing revenue and living standard, expanding jobs opportunities and improving industrial and export development. In line with that goal, one of the agricultural development policy is to develop farm subsector that has been navigate to development of public farm. Farm subsector is a job opportunity that absorb many work force, providing  raw material for processing industry and act in conserving environment, because of that, the effort to develop this subsector need to be increased. The purpose of this research is to know the income of cacao farmers in Bobo Village, knowing the cacao farm business revenue in Bobo Village Palolo Sub-District, Sigi District, was conducted in January – March 2017. Cacao farm business revenue in Bobo Village, Palolo Sub-District, Sigi district. The sampling method used in this research was Simple Random Sampling method, with 30 farmers as sample from 70 of cacao farmers population. Result of this research conclude that the average  of cacao farmers income is Rp. 31.421.939,84/1,42Ha or Rp. 22.128.126,65/Ha, the average of cacao farmers revenue in Bobo Village is Rp. 36.380.000/1,42Ha or Rp. 25.619.718,31/Ha, and the average of total cost of cacao farmers in Bobo Village is Rp. 4.958.060,16/1,42Ha or Rp. 3.491.591,67/Ha.